The slave ship a human history - Rediker, Marcus (New York Penguin Books, 2008)
For more than three centuries, slave ships carried millions of people from the coasts of Africa to the New World. Here, award-winning historian Rediker creates a detailed history of these vessels and the human drama acted out on their rolling decks. Rediker restores the slave ship to its rightful place alongside the plantation as a formative institution of slavery, as a place where a profound and still haunting history of race, class, and modern capitalism was made.--From publisher description.
Life, death, and terror in the slave trade -- The evolution of the slave ship -- African paths to the Middle Passage -- Olaudah Equiano : astonishment and terror -- James Field Stanfield and the floating dungeon -- John Newton and the peaceful kingdom -- The captain's own hell -- The sailor's vast machine -- From captives to shipmates -- The long voyage of the slave ship Brooks -- Epilogue: endless passage.
"First published in the United States of America by Viking Penguin, a member of Penguin Group (USA) Inc. 2007."--Title page verso.
CSSP-6675 donated by The Rotary Club Beaverton, Oregon, United States of America.
Keywords: Slave trade -- Africa -- History; Slaves; Merchant mariners; Race relations; Slave ships -- History